Resource constraints, patient emotions, and therapy: experiences of healthcare providers in the screening and management of gestational diabetes mellitus in northern Ghana - Mohammed Bukari; Abdulai Abubakari; Hawa Malechi; Thomas Hinneh; Humphrey Garti; Faith Agbozo (BMC Health Services Research)
Abstract Background Studies on healthcare providers’ experiences in screening and managing Gestational Diabetes Mellitus (GDM) are rare in northern Ghana. Understanding the experiences of healthcare providers in the screening and management of GDM has the potential to identify best practices to improve GDM care. Hence, this study sought to explore the experiences of healthcare providers in screening and managing GDM. Materials and methods This was a qualitative study of five key informants involved in the screening and management of GDM, specifically an obstetrician, a dietician/nutritionist, a nurse, and two midwives in the northern region of Ghana. Face-to-face interviews were conducted with the aid of an interview guide, and the data were analysed via thematic analysis. We ensured trustworthiness through reflexivity, member checking, peer-debriefing, providing rich text, and keeping an audit trail. Results Two main themes and six subthemes were generated. The first theme was resource-centred experiences, which explored events at the Antenatal Care (ANC) and the challenges in GDM screening and management, with subthemes namely: ANC setups, inadequate resources, and non-compliance. The second theme was care-centred experiences, which explored patient emotions during GDM care, and the care they receive post-GDM diagnosis, with subthemes namely: raw emotions, non-pharmacological therapy, and pharmacotherapy. Conclusion Findings suggest the need for health system strengthening through the training and recruitment of dedicated skilled personnel, as well as government intervention through policy revision to cover the cost of GDM diagnostic tests. Healthcare providers should also consider the psycho-emotional impact of diagnosis when managing GDM. The findings could be relevant for health policy, planning, advocacy, and social and behaviour change communication aimed at effective screening and management of GDM.